Effects of Different Types and Dosage of Green Mulch on Yield and Quality of Aloe vera L. on Coastal Sandy Soil - Maria Theresia Darini (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
A complete content of chemical substance from Aloe vera leaf makes this plant has many functions such as the ingredient of functional food for health, cosmetics, and herbal medicines. This research was aimed to determine the yield and quality of Aloe vera L. on various types and rates of green mulch in coastal sandy soil. The research was conducted in coastal sandy soil of Poncosari Srandakan, Bantul, Yogyakarta and done in a Randomized Complete Block Design (RCBD) of two factors with three replications. The first factor was four types of green mulch (shrimp evergreen, cashew, acasia and gliricidia). The second factor was various rate of green mulch consisted of three levels rates of leave mulch (5.0, 10.0, and 15.0 tons ha-1). Soil without mulching was used as a control treatment. The variables observed were yield at the first harvest time and leaf content quality which includes water, protein, fat, carbohydrate, ash, fiber, and mineral (Ca, Fe and Zn). The results showed that there was interaction between types and rates of leave mulch in all variables observed. Gliricidia leaf mulch gave the best effect with optimum rate about of 10 ton ha-1. The effectiveness of green mulch abilities on improving the observed variables from higher order to low was gliricidia, acasia, cashew and shrimp-type evergreen with the rate range between 10 up to 15 tons ha-1.